2016
DOI: 10.1002/mrm.26394
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and biodistribution of iron oxide nanoparticles in the primary clearance organs of mice using T 1 contrast for heating

Abstract: Purpose To use contrast based on longitudinal relaxation times (T1) or rates (R1) to quantify the biodistribution of iron oxide nanoparticles (IONPs), which are of interest for hyperthermia therapy, cell targeting, and drug delivery, within primary clearance organs. Methods Mesoporous silica-coated IONPs (msIONPs) were intravenously injected into 15 naïve mice. Imaging and mapping of the longitudinal relaxation rate constant at 24 hours or 1 week post-injection were performed with an echoless pulse sequence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 39 publications
1
54
0
Order By: Relevance
“…Initial measurements were focused on the longitudinal relaxation rate constant R 1 (= 1/T 1 ) of a range of silica shell thicknesses at 1 mg Fe mL −1 in 1% agarose (Figure b). The R 1 values for all of the sIONPs are lower than those for uncoated EMG308 and msIONPs 23b. The decrease in R 1 can be attributed to reduced water accessibility to the core.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Initial measurements were focused on the longitudinal relaxation rate constant R 1 (= 1/T 1 ) of a range of silica shell thicknesses at 1 mg Fe mL −1 in 1% agarose (Figure b). The R 1 values for all of the sIONPs are lower than those for uncoated EMG308 and msIONPs 23b. The decrease in R 1 can be attributed to reduced water accessibility to the core.…”
Section: Resultsmentioning
confidence: 79%
“…b) The longitudinal relaxation rate constant (R 1 ) at 9.4T of EMG308, msIONPs, and sIONPs with various shell thicknesses at 1 mg Fe mL −1 . For comparison, the R 1 at 1 mg Fe mL −1 is shown for EMG308 (sIONP with shell thickness = 0 nm) and msIONP 23b. Error bars indicate the standard deviation across the sample and are not visible because they are smaller than the circular marker shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we showed that the addition of 1 to 10 mg Fe/mL VS55 had no further impact on viability ( P < 0.05). In addition, previous data demonstrated that the msIONPs are nontoxic when cultured with HDF over time at low concentration (0.07 mg Fe/mL) (19), and when injected at higher concentration (20 mg Fe/mL in 200 μL) intravenously into mice (31). This biocompatibility is due to both the mesoporous silica coating and the PEG bound to it as described previously (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, coating the IONPs with mesoporous silica has been shown to improve stability [152, 153]. Moreover, this coating has demonstrated a high stability within biological environments and has maintained that stability within CPAs [154, 155]. …”
Section: Bioengineering Applicationsmentioning
confidence: 99%